Myocarditis and pericarditis following mRNA vaccination in autoimmune inflammatory rheumatic disease patients: A single‐center experience. Issue 2 (14th June 2022) - Patel, Shreeya; Wu, Emma; Mundae, Maninder; Lim, Keith
Abstract: Introduction: The mRNA vaccines Comirnaty (Pfizer/BioNTech) and Spikevax (Moderna) are considered safe and highly effective against SARS‐COV2. However, they are also associated with a small increased risk of pericarditis and myocarditis. There is concern about an increased risk of these complications in patients with autoimmune inflammatory rheumatic diseases (AIRD). Case Report: We describe three patients with pre‐existing AIRD who developed myocarditis or pericarditis shortly after receiving their first dose of the Pfizer‐BioNTech vaccine. The first case is a 31‐year‐old female with systemic lupus erythematosus (SLE) and anti‐phospholipid syndrome (APLS) who presented 7 days after receiving the Pfizer‐BioNTech vaccine and was diagnosed with myopericarditis following a positive troponin and abnormal transthoracic echocardiogram (TTE). The second case is a 29‐year‐old man with seronegative inflammatory arthritis and APLS who presented 7 days after receiving the first dose of the Pfizer‐BioNTech vaccine. His troponin and TTE were unremarkable however his ECG showed widespread ST elevation. Lastly, the third case is a 34‐year‐old man with Behcet's disease with a history of recurrent pericarditis. He developed a recurrence of symptoms approximately 7 days after his Pfizer‐BioNTech vaccine and self‐commenced prednisolone at home. He had normal laboratory and radiological findings. All patients received prednisolone resulting in a quick recovery and resolution of symptoms. Discussion: In this review we discuss the association between myocarditis, pericarditis and mRNA COVID‐19 vaccines, those who are at greatest risk and current clinical considerations. We also discuss the possible increased risk in AIRD patients and the current research supporting this. Key points: Myocarditis and pericarditis are recognized side effects of the messenger RNA (mRNA) vaccines Comirnaty (Pfizer/BioNTech) and Spikevax (Moderna). Our observations support the theory that patients with autoimmune inflammatory rheumatic diseases that predisposes them to develop myocarditis/pericarditis, might put them at increased risk of developing this complication after the mRNA vaccine. Abstract : We present three AIRD patients who developed myocarditis or pericarditis approximately seven days after receiving their first dose of the Pfizer‐BioNTech vaccine. All patients made full recovery following a course of prednisolone. This report highlights what we know about the risk of myocarditis or pericarditis following mRNA COVID‐19 vaccines and the potentially increased risk in AIRD patients.